(untitled) (Fiep Bulletin - online, 2014)
The main objective of this study is list the percentile of corporal and body mass índex in Young adults practicing of strength. The research was conducted through the collection of data from individuals of a bodybuilding gym in the city of Maringá/PR. The final sample obtained (n = 80) was divided into 4 groups: group male I (20 subjects, males), group male II (20 subjects, males), group female I (20 subjects, female), and group female II (20 subjects, female), with age between 18 and 38 years, the groups of number 2 are composed of same individuals of groups I, but after a period of training. To the achievement of assessments, were identified the anthropometric measurements, weight, height, body circumferences, skinfold thickness of each individual and the bioimpedance. The data were analyzed through descriptive statistics. After the training period the BMI (body mass index) of the groups female I and II decreased from 21.8 ± 0.41 to 21.57 ± 0.42 alread the %BF (percentile of corporal fat) has undergone a drop of 28.13 ± 0.95 to 26.29 ± 0.87, this was not considered overweight, being below the cutoff point indicated by the World Health Organization, but the %BF points to the overweight being within the cutoff point 25% to 30% for females. In the male groups the same happens, there was a decline in BMI of the male groups I and II 24.98 ± 0.78 to 24.55 ± 0.65alread the %BF also suffered a decline of 19.02 ± 1.37 to 17.23 ± 1.08, the BMI of the groups I and II do not indicate overweight already the %BF points to the overweight being within the cutoff point of 15.0% and 20.0% for male. Is important to quantify body fat with minimum error, in order to control the volume of body fat in relation to human health, the factor that limits the use of BMI is the fact that he is not able to provide information associated with body composition thus subjects with a large amount of muscle mass can display the BMI so as high even if, body fat it is not too much.